Method for creating functional aerogel carbon high-long-acting purification material based on waste disposable masks
By mixing the broken polypropylene non-woven fabric with PVA and CMC solutions and adding bayberry tannins and metal compounds, aerogel carbon material with a metal polyphenol network structure was prepared, which solved the treatment of waste masks and antibiotic wastewater purification. Problem, efficient degradation of antibiotic wastewater and resource utilization have been achieved.
Patent Information
- Application Number
- CN202411270194.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-17
AI Technical Summary
There are environmental pollution problems in the treatment of waste disposable medical masks and purification of antibiotic wastewater, and it is difficult for the existing technology to effectively utilize waste mask resources and improve the catalytic performance of carbon materials.
By mixing the broken polypropylene nonwoven fabric with PVA and CMC solutions, adding bayberry tannins and metal compounds, ultrasonic mixing, freeze-drying and high-temperature pyrolysis, aerogel carbon material with a metal polyphenol network structure was prepared. , used to activate persulfate degradation of antibiotic wastewater.
It has achieved efficient degradation of antibiotics, low cost, low material toxicity, good degradation performance of activated persulfate, can quickly catalyze pollutant degradation, resource utilization of waste masks, and improved the activation efficiency of carbon materials.
Smart Images

Figure CN119318920A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the preparation of composite functional aerogel carbon materials and the field of antibiotic wastewater purification, specifically a method for creating functional aerogel carbon high-long-acting purification materials based on discarded disposable masks as a carbon source. Background Art
[0002] Currently, disposable medical masks are used and consumed in significant quantities in daily life, experimental research, and clinical settings. Scientifically and environmentally soundly disposing of these discarded masks is a significant challenge facing countries and regions worldwide, as well as a pressing need for ecological and environmental protection and sustainable resource utilization. Discarded disposable medical masks primarily consist of polypropylene nonwoven fabric. Modifying and compounding the polypropylene nonwoven fabric used in the middle layer of shredded disposable masks has the potential to create functional aerogel carbon materials using these discarded masks as a carbon source.
[0003] On the other hand, the large-scale use of antibiotics and the discharge of improper treatment and disposal have led to serious water pollution. Removing such antibiotics from the water environment is extremely important for protecting the environment and human health. In recent years, the removal of organic pollutants in water by advanced oxidation technologies such as activated persulfate degradation and Fenton has attracted much attention. Persulfate activation methods include thermal activation, metal ion activation, carbon material activation and electroactivation. Carbon materials have a relatively large specific surface area and low cost. Currently, carbon materials such as activated carbon and graphene have been widely used in wastewater adsorption and catalysis. By modifying carbon materials, it is expected that the catalytic performance of carbon materials will be further improved, and their activation efficiency in advanced oxidation reaction processes will be improved. By constructing a metal polyphenol network structure for carbon materials through metal grafting, the catalyst can achieve the combination of transition metal elements and carbon material catalysis, which is expected to achieve an improvement in activation ability.
[0004] Furthermore, this material uses polypropylene, a raw material used in disposable medical masks, as a carbon source. By mixing it with bayberry tannin to dissolve and chelate metal ions, it can form a carbon aerogel with a metal polyphenol network. This also achieves high-value utilization of waste polypropylene materials, which has environmental benefits. Therefore, to address the above issues, a method for creating a functional aerogel carbon with high-efficiency and long-lasting purification material using disposable medical masks is proposed. Summary of the Invention
[0005] The purpose of the present invention is to realize the resource utilization of discarded disposable masks and provide a method for creating a functional aerogel carbon high-long-term purification material based on discarded disposable medical masks as a carbon source, so as to solve the problems raised in the above background technology.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for creating a functional aerogel carbon high-long-term purification material based on discarded disposable medical masks as a carbon source, comprising the following steps:
[0008] Step 1: Prepare functional carbon aerogel precursor solution: Weigh 5g of PVA and dissolve it in 100ml of water to prepare PVA solution, and prepare 1.0wt% CMC solution. Weigh the powder of the crushed middle layer of discarded masks and disperse it in a fixed ratio of PVA solution and CMC solution;
[0009] Step 2: Preparation of functional aerogel metal grafted substrate: Weighing bayberry tannin and metal compound powder and dissolving them in the precursor solution, ultrasonically mixing and then heating and curing;
[0010] Step 3: freeze-drying the product obtained in step 2 to obtain a polypropylene aerogel having a metal polyphenol network;
[0011] Step 4: The freeze-dried aerogel is evenly dispersed on the bottom of the porcelain ark, placed in a tubular furnace, and pyrolyzed at high temperature under argon protection, and then naturally cooled to room temperature to obtain a carbon aerogel material for activating PDS.
[0012] As a preferred embodiment, in step 1, the mass ratio of PVA to CMC solution in the obtained precursor solution is 1:1.
[0013] As a preferred solution, in step 2, the ultrasonic mixing time is 20 minutes, and the curing is carried out by heating at 100° C. for 2 hours.
[0014] As a preferred solution, in step three, the freeze-drying treatment is specifically as follows: the product obtained in step two is placed in a refrigerator for pre-freezing for 12 hours, and then placed in a freeze dryer for freeze-drying for 24 hours.
[0015] As a preferred solution, in step 4, the specific operation of high-temperature pyrolysis is: heating to the selected calcination temperature at a heating rate of 1-5°C / min under a pure argon atmosphere, maintaining at the selected calcination temperature for 2 hours, and then naturally cooling to room temperature.
[0016] The aerogel, formed by crosslinking polypropylene powder from the crushed middle layer of discarded masks with a PVA and CMC solution, exhibits a broad hydrophilicity group, facilitating the grafting of metal polyphenols onto tannins. After freeze-drying, this material exhibits a large specific surface area and a rich porous structure, enhancing the efficiency of carbon material activation during the PDS activation process. Furthermore, the metal components in this material form a polyphenol network with bayberry tannins, resulting in excellent stability. Combining this with carbon materials further facilitates material recycling and recovery. Consequently, this material exhibits excellent persulfate degradation performance, enabling rapid catalytic degradation of pollutants.
[0017] It can be seen from the technical solution provided by the present invention that the method provided by the present invention for creating a functional aerogel carbon high-long-term purification material based on discarded disposable masks as a carbon source has the following advantages and innovations:
[0018] 1. The present invention is low-cost and easy to obtain, can realize the resource utilization of solid waste, and is environmentally friendly and resource-saving. The synthesis steps are simple, the synthetic materials are low in toxicity, the requirements for reaction conditions and facilities are low, the reaction process is mild and controllable, and it shows a good activation effect on persulfate degradation;
[0019] 2. The material prepared by the present invention is based on the metal grafting of bayberry tannins, forming a unique metal polyphenol network structure. Polyphenols can assemble into polyphenol-metal coordination complexes by capturing metal compounds. At the same time, the exposed surface of the plant polyphenol macromolecules can be protected from further etching by the coating material, enhancing stability and preventing shell collapse. The porous structure of the material can be adjusted by adjusting the reaction time and reactant dosage, achieving a good combination of carbon materials and metal ions, and improving activation performance.
[0020] 3. The functional aerogel carbon nanomaterial prepared by the present invention based on discarded disposable masks as a carbon source can achieve a degradation efficiency of 97.8% for 5 mg / L oxytetracycline within 60 minutes, and has a good activation effect on the degradation of various types of antibiotics. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a scanning electron microscope image of PP@PVA-CMC-Mg-800 aerogel material;
[0022] Figure 2 The FT-IR images of the polypropylene powder, bayberry tannin powder, PP@PVA-CMC and PP@PVA-CMC-Mg after the middle layer of the discarded mask was crushed;
[0023] Figure 3 is the XRD pattern of PP@PVA-CMC-Mg materials at different calcination temperatures (scanning range: 5°-80°, step size: 0.02°, scanning rate: 8° / min);
[0024] Figure 4 It is a comparison of the degradation performance of oxytetracycline by PDS activated by adding PP@PVA-CMC-Mg-800 and without adding materials;
[0025] Figure 5 is a comparison of the performance of oxytetracycline degradation by PP@PVA-CMC-Mg activated PDS at different calcination temperatures;
[0026] Figure 6It is a comparison of the degradation performance of oxytetracycline by PP@PVA-CMC-Mg-800 activated by PDS at different PDS concentrations;
[0027] Figure 7 This is a comparison of the performance of PP@PVA-CMC-Mg-800 activated PDS in degrading different types of antibiotics. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0029] In order to better understand the above technical solution, the above technical solution will be described in detail below with reference to the accompanying drawings and specific implementation methods.
[0030] Example:
[0031] like Figure 1-4 As shown, an embodiment of the present invention provides a method for creating a functional aerogel carbon high-long-term purification material based on discarded disposable masks as a carbon source, comprising the following steps:
[0032] Step 1: Prepare a functional aerogel precursor mixed solution: weigh 5g of PVA and dissolve it in 100ml of water to prepare a PVA solution, and prepare a 1.0wt% CMC solution. Weigh the polypropylene powder after crushing the middle layer of the discarded mask and disperse it in a fixed ratio of PVA solution and CMC solution. The mass ratio of PVA solution to CMC solution in the precursor solution is 1:1;
[0033] Step 2: Preparation of functional aerogel metal grafted substrate: Weigh bayberry tannin and metal compound powder and dissolve them in the precursor solution, ultrasonically mix and then heat-curing treatment, wherein the ultrasonic time is 20 minutes, the heating temperature is 100°C, and the curing time is 2 hours;
[0034] Step 3: freeze-dry the product obtained in step 2 to obtain a polypropylene aerogel with a metal polyphenol network, wherein the aerogel is frozen in a refrigerator for 12 hours and then placed in a freeze vacuum drying oven for 24 hours;
[0035] Step 4: Evenly disperse the dried precursor on the bottom of the porcelain ark, place it in a tubular furnace, perform high-temperature pyrolysis under argon protection, and then naturally cool to room temperature to obtain aerogel carbon nanomaterials. The specific operation of high-temperature pyrolysis is: in a pure argon atmosphere, heat to 800°C at a heating rate of 1-5°C / min, maintain at this temperature for 2 hours, and then naturally cool to room temperature.
[0036] The present invention relates to a method for creating functional aerogel carbon nanomaterials based on discarded disposable masks as a carbon source, and the application of aerogel carbon nanomaterials in activating peroxydisulfate (PDS) to efficiently degrade and purify antibiotic wastewater.
[0037] The active material described in the present invention is abbreviated as PP@PVA-CMC-Mg.
[0038] The pollutant degraded by the present invention is oxytetracycline, and the pollutant concentration is 5 mg / L.
[0039] The antibiotic pollutant described in the present invention is oxytetracycline wastewater with different concentrations (2mmol / L, 4mmol / L, 6mmol / L, 8mmol / L, 10mmol / L), the addition amount of aerogel carbon nanomaterial is 0.25g / L, and magnetic stirring is performed at room temperature.
[0040] The sampling time points described in the present invention are 5, 10, 15, 30, 45, and 60 minutes.
[0041] The sampling method involved in the present invention requires filtering the liquid using a filter membrane after sampling is completed at the sampling time point.
[0042] The pollutant detection method described in the present invention is to use an ultraviolet spectrophotometer to measure the absorbance of the pollutants and perform ratio measurement before and after the reaction.
[0043] The catalysts described in the present invention are all tested at room temperature to prevent large temperature changes from affecting the catalyst performance.
[0044] The present invention will be further described below with reference to specific examples. In order to further understand the present invention, preferred embodiments of the present invention will be described with reference to the examples. However, it should be understood that these descriptions are intended only to further illustrate the features and advantages of the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the disclosure of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope of protection defined by the present invention.
[0045] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; the reagents, materials, etc. used in the following examples are all commercially available unless otherwise specified.
[0046] Example 1:
[0047] This implementation case demonstrates a method for creating a functional aerogel carbon high-long-term purification material (PP@PVA-CMC-Mg) based on discarded disposable masks as a carbon source, as well as the application of aerogel-activated peroxydisulfate (PDS) to degrade antibiotic wastewater.
[0048] The pollutant degraded by the present invention is oxytetracycline, and the pollutant concentration is 5 mg / L.
[0049] In the present invention, the effects of different concentrations of oxytetracycline wastewater (2mmol / L, 4mmol / L, 6mmol / L, 8mmol / L, 10mmol / L) on the purification effect were investigated. The dosage of the aerogel carbon nanoparticle purifier was 0.25g / L, a rotor was added, and the purification was carried out on a magnetic stirrer at room temperature.
[0050] The sampling time points of the pollutant degradation process of the present invention are 5, 10, 15, 30, 45, and 60 minutes, and the obtained samples need to be filtered using a filter membrane.
[0051] The pollutant detection method described in the present invention is to use an ultraviolet spectrophotometer to measure the absorbance of the pollutants and perform ratio measurement before and after the reaction.
[0052] The catalysts described in the present invention are all tested at room temperature to prevent large temperature changes from affecting the catalyst performance.
[0053] (1) Preparation of an aerogel precursor mixed solution using discarded disposable masks as a carbon source: 5 g of PVA was weighed and dissolved in 100 ml of water to prepare a PVA solution, and a 1.0 wt% CMC solution was prepared. 1 g of mask powder with polypropylene as the main component was weighed and dispersed in a fixed ratio of PVA solution and CMC solution to prepare 50 g of a precursor mixed solution;
[0054] (2) Preparation of functional aerogel metal grafted substrate: 0.5 g of bayberry tannin and 0.001 mol MgSO4·7H2O were weighed and mixed with the precursor solution, ultrasonicated for 20 min, and then heated and cured at 100 °C for 2 h;
[0055] (3) freeze-drying the product obtained in (2) to obtain the metal-grafted mask aerogel, pre-freezing it in a refrigerator for 12 hours and then placing it in a freeze vacuum drying oven for freeze-drying for 24 hours;
[0056] (4) The dried precursor was evenly dispersed on the bottom of the porcelain ark, placed in a tubular furnace, and heated to 800°C at a heating rate of 1-5°C / min under argon protection. After maintaining at this temperature for 2 hours, it was naturally cooled to room temperature to obtain a functional aerogel carbon nanoparticle purification material based on discarded disposable medical masks as a carbon source.
[0057] The PP@PVA-CMC-Mg aerogel carbon nano-purification material obtained in this example was subjected to phase identification and micromorphology and structure characterization: a powder X-ray diffractometer was used to identify the phase of the prepared material, a Fourier transform infrared spectrometer was used to analyze the functional groups of the material, and a scanning electron microscope was used to characterize the micromorphology and structure of the obtained material.
[0058] Figure 1 This is a scanning electron micrograph of the aerogel carbon nanoparticle purification material loaded with magnesium metal and calcined at 800°C. The image shows the material's rich porous structure, uneven surface, and large specific surface area. This indicates that the free hydrogen released by the plant polyphenols has penetrated the metal polyphenol network and etched it, forming a porous structure within the aerogel and exposing more active sites.
[0059] Figure 2 The FT-IR images of polypropylene powder, bayberry tannin powder, PP@PVA-CMC, and PP@PVA-CMC-Mg after the middle layer of discarded masks was crushed show that the physical crosslinking of PVA and CMC successfully modified polypropylene, and hydroxyl groups that can be used for metal grafting were obtained, proving that the material can achieve metal grafting through tannin.
[0060] Figure 3 This is the XRD pattern of PP@PVA-CMC-Mg material at different calcination temperatures (scanning range: 5°-80°, step size: 0.02°, scanning rate: 8° / min). It can be seen that the peak belonging to MgO is most obvious at 800°C, indicating that the crystallization state is better at this time. The material can better exert its activation performance under calcination conditions at 800°C.
[0061] Figure 4 The performance of oxytetracycline degradation is compared between no material added and PP@PVA-CMC-Mg-800 added. It can be seen that when the traditional commercial PDS activator is added alone without other activation measures, the oxytetracycline degradation rate within 60 minutes is low. After adding PP@PVA-CMC-Mg-800 for synergistic activation treatment, the removal rate of pollutants can reach more than 97%, achieving a significant improvement in degradation effect, which illustrates the activation ability of the material.
[0062] Example 2:
[0063] This implementation case demonstrates a method for creating a functional aerogel carbon high-long-lasting purification material (PP@PVA-CMC-Mg) based on medical disposable masks as a carbon source, as well as the application of aerogel carbon nano-purification materials in degrading antibiotic wastewater.
[0064] In order to explore the optimal preparation method and feasible application range of this material, further factor analysis was carried out based on influencing factors such as calcination temperature, activator concentration and different pollutants.
[0065] Figure 5The performance comparison of oxytetracycline degradation by PP@PVA-CMC-Mg activated peroxydisulfate (PDS) at different calcination temperatures (oxytetracycline concentration of pollutant is 5 mg / L, PDS concentration is 6 mmol / L, and material dosage is 0.25 g / L) shows that the material has the best performance in activating PDS to degrade oxytetracycline at a calcination temperature of 800 °C, which is comparable to the Figure 3 This is consistent with the case where the crystallinity is best at 800°C.
[0066] Figure 6 The performance comparison of oxytetracycline degradation by PP@PVA-CMC-Mg-800 activated by PDS at different PDS concentrations (oxytetracycline concentration of pollutant is 5 mg / L, calcination temperature is 800℃, and material dosage is 0.25 g / L) shows that the catalytic effect shows a trend of first increasing and then decreasing when the PDS concentration changes from 2 mmol / L to 10 mmol / L. This is because the ion concentration involved in the reaction is low due to the low PDS concentration, while the side reaction will occur at a high PDS concentration, generating S2O8. — ·With SO4 2- Leading to SO4 - The content decreases, which in turn reduces the removal efficiency. Therefore, the optimal PDS concentration is 6 mmol / L.
[0067] Figure 7 This is a comparison of the performance of PP@PVA-CMC-Mg-800 activated PDS in degrading different types of antibiotics (pollutant concentration is 5 mg / L, material calcination temperature is 800℃, PDS concentration is 6 mmol / L, and material dosage is 0.25 g / L). The pollutants compared are tetracycline, oxytetracycline, chloramphenicol, sulfamethoxazole, and norfloxacin. It can be seen that the PDS activation effect of this material can achieve the degradation of multiple types of antibiotics, among which the degradation effect of tetracycline antibiotics is the best.
[0068] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. A method for creating a functional aerogel carbon high-long-acting purification material based on discarded disposable masks as a carbon source, characterized in that: The following steps are involved: Step 1: Prepare a precursor solution using discarded disposable masks as a carbon source: weigh 5g of PVA and dissolve it in 100ml of water to prepare a PVA solution, and prepare a 1.0wt% CMC solution, weigh the crushed powder of the middle layer of the discarded mask and disperse it in a fixed ratio of PVA solution and CMC solution and mix them; Step 2: preparing a functional aerogel metal grafted substrate: weighing bayberry tannin and metal compound powder and dissolving them in a precursor solution, and then performing a heating and curing treatment after ultrasonic mixing; Step 3: freeze-drying the product obtained in step 2 to obtain a polypropylene aerogel having a metal polyphenol network; Step 4: The freeze-dried aerogel is evenly dispersed on the bottom of the porcelain ark, placed in a tubular furnace, and pyrolyzed at high temperature under argon protection, and then naturally cooled to room temperature to obtain a carbon aerogel material for activating PDS.
2. According to claim 1, a method for creating a functional aerogel carbon high-long-acting purification material based on a medical disposable mask as a carbon source is characterized by: In step 1, the mass ratio of PVA to CMC solution in the obtained precursor solution is 1:
1.
3. According to claim 1, a method for creating a functional aerogel carbon high-long-acting purification material based on a medical disposable mask as a carbon source is characterized by: In step 2, the ultrasonic mixing time is 20 minutes, and the curing is carried out by heating at 100° C. for 2 hours.
4. A method for creating a functional aerogel carbon high-long-acting purification material based on a medical disposable mask as a carbon source according to claim 1, characterized in that: In step three, the freeze-drying treatment is specifically as follows: the product obtained in step two is placed in a refrigerator for 12 hours, and then placed in a freeze dryer for 24 hours of freeze-drying treatment.
5. The method for creating a functional aerogel carbon high-long-acting purification material based on discarded disposable masks as a carbon source according to claim 1, characterized in that: In step 4, the specific operation of high-temperature pyrolysis is: heating to 500-800°C at a heating rate of 1-5°C / min under a pure argon atmosphere, maintaining at the selected calcination temperature for 2 hours and then naturally cooling to room temperature.
6. An aerogel purification material produced using discarded disposable masks obtained by the preparation method according to any one of claims 1 to 5 as raw materials.
7. An application of aerogel carbon material produced by using the discarded disposable masks described in claim 6 as raw materials in degrading antibiotic wastewater.
Citation Information
Patent Citations
Reutilization method for pyrolytic carbides of municipal domestic wastes
CN106362689A
Preparation method of graphene-based PEI-mGO / CMC / PVA three dimensional composite material
CN108620045A
High-adsorption porous carbon supported zero-valent iron catalyst as well as preparation method and application thereof
CN109999753A
Preparation method of aerogel carbon electrode material based on waste masks
CN117364119A